The Effect of Saccharomyces cerevisiae Addition on the Antioxidant Activity of Arabica Coffee Beans (Coffea arabica) using Natural Fermentation Method - Fansukri, Abdullah Haekal Marzie; Novelina, Novelina; Nazir, Novizar (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2024)
Coffee is not only a regular consumption but can also be said to be part of today's lifestyle. However, despite the popularity of coffee products among the public, many people do not know the contents of coffee which are beneficial for the body. There are many antioxidant compounds in coffee, and antioxidants are an antidote to free radicals, inhibiting oxidation. The post-harvest process of coffee and the fermentation process during post-harvest coffee can affect the content and compounds contained in coffee. Fermentation generally uses bacteria, fungi, and yeast. The type of yeast used in research is Saccharomyces cerevisiae; its metabolic products can influence the antioxidant content of coffee beans. This research aims to determine the effect of Saccharomyces cerevisiae concentration on antioxidant activity in coffee beans. This research treatment consisted of without the adding starter (A), fermentation with a concentration of 1.5% (B), fermentation with a concentration of 2% (C), fermentation with a concentration of 2.5% (D), fermentation with a concentration of 3% (E). The data obtained were analyzed statistically using ANOVA and continued with DNMRT at the 5% level. Chlorogenic acid and caffeine were tested using High-Performance Liquid Chromatography (HPLC) to determine how much of these compounds are contained in the coffee beans. The results of this research show that differences in Saccharomyces cerevisiae concentrations significantly affect the 5% level of the degree of acidity (pH) and antioxidant activity. The best treatment was obtained in treatment E, with a pH value of 5.9 and antioxidant activity of 54.72%.